Begonia glutinosa, a new synonym of Begonia wallichiana (Begoniaceae) with additional notes on this species - Radbouchoom, Sirilak; Chen, Wen-Hong; Shui, Yu-Min (Phytotaxa, 2017)
Based on examination of type specimens and publications, we confirmed that Begonia glutinosa Kiew from Vietnam is conspecific to B. wallichiana Lehm. Thus, we combined B. glutinosa as a new synonym of B. wallichiana Lehm.. As to B. wallichiana, the complicated history of taxonomic revision and botanic nomenclature is discussed here.